IoT Market Size and Demand - Isa, Khalid (Evolution of Information, Communication and Computing System, 2022)
Internet of Things (IoT) envisages that everything in the physical world is seamlessly connected and securely integrated via the Internet infrastructure. Data can be collected and converted into useful information as things respond to the environment or stimuli, which can be used in different application domains such as automated home appliances, smart grids, smart manufacturing, etc.